Outcomes of music therapy interventions in cancer patients—A review of the literature. (June 2019) - Gramaglia, Carla; Gambaro, Eleonora; Vecchi, Camilla; Licandro, Davide; Raina, Giulia; Pisani, Carla; Burgio, Vincenzo; Farruggio, Serena; Rolla, Roberta; Deantonio, Letizia; Grossini, Elena; Krengli, Marco; et al.
Graphical abstract: Highlights: Music-based interventions (MBIs) can be subdivided in Music Therapy (MT) and Music Medicine (MM). MBIs have positive effects on cancer patients' anxiety, depression, pain, life quality of life. MT interventions are particularly effective on anxiety. Greater reductions of anxiety and depression are observed in breast cancer. MT involving patients admitted to a hospital ward seem less effective in life quality improvement. Abstract: Background: Effectiveness of music-based interventions (MI) on cancer patients' anxiety, depression, pain and quality of life (QoL) is a current research theme. MI are highly variable, making it challenging to compare studies. Objective and methods: To summarize the evidence on MI in cancer patients, 40 studies were reviewed following the PRISMA statement. Studies were included if assessing at least one outcome among anxiety, depression, QoL and pain in patients aged ≥ 18, with an active oncological/onco-haematological diagnosis, participating to any kind of Music Therapy (MT), during/after surgery, chemotherapy or radiotherapy. Results: A positive effect of MI on the outcomes measured was supported. Greater reductions of anxiety and depression were observed in breast cancer patients. MI involving patients admitted to a hospital ward were less effective on QoL. Conclusion: The increasing evidence about MI effectiveness, tolerability, feasibility and appreciation, supports the need of MI implementation in Oncology, Radiotherapy and Surgery wards, and promotion of knowledge among health operators.